Dinamika Hutan Alam Produksi : Pendekatan Kuantitatif - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
ABSTRACT No management prescription on a forest area can succeed without sufficient basis on its dynamics. On the other hand, forest dynamics inherently complicates several factors such as stand status (density, stock, site, structure, composition, age) time elapsed, and silvicultural treatment. When the problem is complicated, then quantitative approach gains its role. In this paper, both stochastic and deterministic methods applied to natural forest dynamics were discussed. While the uses of stochastic method, based on statistical distribution functions, may give a measure on the precision of the estimates, its applications are constrained by complications in deriving joint, and sometimes truncated distribution functions. Deterministic method was proven to be more applicable in anticipating Indonesian forestry situation. To some extent, the model can be simplified in terms of data types to be provided. The model can then be harmoniously integrated into more comprehensive mathematical programming. If the data can be provided, then it will produce sound and dependable projections and recommendations for the forest managers